Cover Picture: Implementing a second generation CCS facility on a coal fired power station – results of a feasibility study to retrofit SaskPower's Shand power station with CCS (Greenhouse Gas Sci Technol 3/2020). Issue 3 (27th June 2020) - Giannaris, Stavroula; Bruce, Corwyn; Jacobs, Brent; Srisang, Wayuta; Janowczyk, Dominika
Abstract : The cover image is based on the Spotlight Implementing a second generation CCS facility on a coal fired power station – results of a feasibility study to retrofit SaskPower's Shand power station with CCS by Stavroula Giannaris et al., https://doi.org/10.1002/ghg.1989 .